Immunohistochemical analysis of T‐type calcium channels in acquired melanocytic naevi and melanoma. (20th March 2017) - Maiques, O.; Macià, A.; Moreno, S.; Barceló, C.; Santacana, M.; Vea, A.; Herreros, J.; Gatius, S.; Ortega, E.; Valls, J.; Chen, B.J.; Llobet‐Navas, D.; et al.
Summary: Background: Cutaneous malignant melanoma arises from transformed melanocytes de novo or from congenital or acquired melanocytic naevi. We have recently reported that T‐type Ca 2+ channels (TT‐Cs) are upregulated in human melanoma and play an important role in cell proliferation. Objectives: To describe for the first time in formalin‐fixed paraffin‐embedded tissue the immunoexpression of TT‐Cs in biopsies of normal skin, acquired melanocytic naevi and melanoma, in order to evaluate their role in melanomagenesis and/or tumour progression, their utility as prognostic markers and their possible use in targeted therapies. Methods: Tissue samples from normal skin, melanocytic naevi and melanoma were subjected to immunohistochemistry for two TT‐Cs (Cav3.1, Cav3.2); markers of proliferation (Ki67), the cell cycle (cyclin D1), hypoxia (Glut1), vascularization (CD31) and autophagy (LC3); BRAF V600E mutation (VE1) and phosphatase and tensin homologue (PTEN). Immunostaining was evaluated by histoscore. In silico analysis was used to assess the prognostic value of TT‐C overexpression. Results: TT‐C immunoexpression increased gradually from normal skin to common naevi, dysplastic naevi and melanoma samples, but with differences in the distribution of both isoforms. Particularly, Cav3.2 expression was significantly higher in metastatic melanoma than in primary melanoma. Statistical correlation showed a linear interaction between PTEN loss/BRAF V600E/Cav3.1/LC3/ Ki67/cyclin D1/Cav3.2/Glut1. Disease‐free survival (DFS) and overall survival correlated inversely with overexpression of Cav3.2. DFS also correlated inversely with overexpression of Cav3.1. Conclusions: TT‐C immunoexpression on melanocytic neoplasms is consistent with our previous in vitro studies and appears to be related to tumour progression. TT‐C upregulation can be considered as a prognostic marker using The Cancer Genome Atlas database. The high expression of Cav3.2 in metastatic melanoma encourages the investigation of the use of TT‐C blockers in targeted therapies. Abstract : What's already known about this topic? Increased expression of voltage‐gated calcium channels is a common finding in several neoplasms. We have recently reported that T‐type Ca 2+ channels (TT‐Cs) are upregulated in human melanoma cells and play an important role in cell proliferation, calcium homeostasis and autophagic flux. What does this study add? TT‐C immunoexpression increases gradually from normal skin to common naevi, dysplastic naevi and melanoma samples, and expression of the Cav3.2 isoform is augmented in metastatic vs. primary melanoma. We demonstrate a significant correlation between Breslow thickness and TT‐C expression, and show a positive correlation between the immunoexpression of Cav3.2 and proliferative/hypoxia markers. We show a positive association between the expression of the Cav3.1 isoform, the autophagy markers and the presence of the BRAF V600E mutation. What is the translational message? These findings open a new avenue of research regarding the use of T‐type blockers in targeted therapies. Linked Comment:Ellis. Br J Dermatol 2017; 176:1122 Plain language summary available online